Barbie. Dreamtopia [videorecording (DVD)] - Cogan, Michelle; Pistor, Julia; Blinkoff, Saul Andrew; Boutilier, Kate; Symonds, Aaron (NCircle Entertainment, 2021)
Join Barbie, Chelsea, and her puppy Honey as they swim through rainbow rivers with beautiful mermaids and fly through cotton candy clouds with fairies. All you have to do is dream!